Funding University Education In Nigeria: Implications On Institutional Performance - Agha Ph.D, Nancy Chinwe (International Journal of Scientific Research and Management (IJSRM), 2014)
The problem of funding of universities in Nigeria has become a recurring decimal often resulting into strikes and closures of universities. The trend led to slow infrastructural development, inadequate teaching and learning facilities, brain drain and general falling standard of Education. The paper examined funding university Education in Nigeria and its implications on the performance of these institutions. The African political economy model was used in explaining the financial state of Nigerian Universities. While the human capital theory was used to support the arguments in favour of multiple forms of cost sharing. The findings revealed that although the Federal Government provides about 90 percent funds, it has not been able to successfully finance the system due to economic, social and political depression. This is evident in poor quality of teaching and research, poor conditions of work and insufficient attention to staff development. The consequence is that goals of university education in Nigeria are yet to be achieved. The paper recommended that the federal government of Nigeria should increase budgetary allocation to the education sector significantly on yearly basis. It further recommended the partial deregulation of education sector so as to ensure the provision of additional reserves for universities.